Tipologi Transformasi Fasad Rumah Bantuan Pasca Tsunami di Desa Deah Baro, Kecamatan Meuraxa, Banda Aceh, Indonesia - Zamzami; Marlisa Rahmi; Maysarah Binti Bakri (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Meuraxa sub-district was one of the areas significantly affected by the 2004 Aceh tsunami. After the disaster, housing assistance was provided by variousinternationalagencies and organizations, in the same location. Initial observation indicate changes in the facades of the aid houses. Threfore, ths study aims to identify the factors that causedthe transformation of the facade and to determine the dominant elements that underwenttransformation in post-tsunami relief houses in Meuraxa Sub-district, Banda Aceh.